2014
DOI: 10.1177/0009922814558256
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Conservative Protocol to Return Children and Youth to Activity Following Concussive Injury

Abstract: Implementation of these new pediatric recommendations is an important addition to prevention of subsequent concussions during vulnerable recovery periods, with potential to facilitate recovery by preventing prolonged symptomatology, and secondary sequelae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 62 publications
0
42
0
Order By: Relevance
“…The review of 400 possible articles included information from 10 studies and 3 Web sites; however, none of the guidelines were specific to the younger population. As a result of these findings, follow-up studies using the National Institute of Health and Care Excellence procedures were conducted to develop pediatric-specific return-to-activity 66 and return-toschool 65 protocols. These protocols take a more conservative approach, strive to find a balance between allowing the brain to heal and addressing the need to participate in some activity, and emphasize that different pathways are likely required during the recovery process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The review of 400 possible articles included information from 10 studies and 3 Web sites; however, none of the guidelines were specific to the younger population. As a result of these findings, follow-up studies using the National Institute of Health and Care Excellence procedures were conducted to develop pediatric-specific return-to-activity 66 and return-toschool 65 protocols. These protocols take a more conservative approach, strive to find a balance between allowing the brain to heal and addressing the need to participate in some activity, and emphasize that different pathways are likely required during the recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…These protocols take a more conservative approach, strive to find a balance between allowing the brain to heal and addressing the need to participate in some activity, and emphasize that different pathways are likely required during the recovery process. 66 After the development of the protocols, pilot testing was conducted with health care providers, and all strongly agreed that using the protocol changed their clinical practice, increased their knowledge, and enhanced their confidence in treating children with concussion. 66 Similar findings were noted among health care providers who pilot tested the return-toschool protocol: 95% strongly agreed that the protocol gave specific and clear directions for applying the recommenda-tions, 80% indicated that it increased their knowledge, and 85% strongly agreed that their confidence in managing children with concussion improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,20 However, the need for a child-specific protocol has previously been established. 52,53 Based on the 2013 Zurich Consensus Statement, 1 a number of organisations throughout the world have developed guidelines to facilitate post-concussion management by medical practitioners (Table 1). [54][55][56][57][58][59][60] They offer different recommendations for the management of adults and children.…”
Section: Implications For Concussion Management and Return To Sport Pmentioning
confidence: 99%
“…The AIS/AMA position statement errs on the side of caution, given the lack of clear scientific evidence and the need to provide safe advice to the grass-roots sporting community. 53 However, management should be according to the pattern of recovery 53 and individualised clinical judgement will continue to influence management decisions. 2 Concussion research progresses at a fast pace and the synthesis of new studies into clear evidence-based protocols in a timely manner is challenging; however, a major effort is being made to regularly translate research to guidelines for clinical practice.…”
Section: Implications For Concussion Management and Return To Sport Pmentioning
confidence: 99%